The Effect of Leadership, Adversity Quotient on Organizational Commitment of PT. Jaya Konstruksi Manggala Pratama Tbk - Sugeng Subagyo; Makruf Akbar; Wibowo Wibowo (IJEBD International Journal Of Entrepreneurship And Business Development eISSN 2597-4785 pISSN 2597-4750)
Purpose: The purpose of this study was to describe and analyze the influence of corporate leadership, adversity quotient on organizational commitment. Design/methodology/approach: This research used a quantitative approach with survey method. The sample of this research is the whole 204 staff in PT. Jaya Konstruksi Manggala Pratama Tbk is done randomly. Findings: 1) there is a direct positive influence leadership on organizational commitment; (2) there is a direct positive influence adversity quotient on organizational commitment; (3) there is a direct positive influence to adversity quotient against leadership; (4) there is a indirect positive influence leadership on organizational commitment through adversity quotient Research limitations/implications: is the whole 204 staff in PT. Jaya Konstruksi Manggala Pratama Tbk. Practical implications: describing and analyzing the influence of corporate leadership, adversity quotient on organizational commitment. Paper type: Research paper